Pemetaan Efektivitas dan Efisiensi Metode Desain Produk: Telaah Pustaka - Widyastuti Widyastuti; Erni Suparti; Alva Edy Tontowi (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
Identification of user needs and their conversion into product specifications is an important stage in the product design process. The large number of design methods currently available is a challenge for designers in choosing an effective and efficient design method. The aim of this literature review was to identify the use of product design methods between 2019-2023, mapped the effectiveness and efficiency of existing product design methods. Identification process used bibliometric analysis of articles in the SCOPUS database. VOSviewer software was used in the analysis process with co-occurence type and full-counting calculation methods. Effectiveness mapping was based on 7 criteria (E1 - E7) and efficiency based on 3 criteria (F1 - F3). The identification results show that the design methods that have been widely used in the last five years were value engineering, quality function deployment, user centered design, universal design, kansei engineering and TRIZ. The mapping results show that effective and efficient methods were QFD and value engineering. The effectiveness and efficiency of other methods were explained in more detail in this review.